Representation of ‘Dark Indonesia’ Student Protests in Voice of America’s English News: A Transitivity Analysis - Masy'al, Kayla Nurfayza (Universitas Sebelas Maret, 2025)
Student protests have recently become a source of political polemic among society that is often influenced by how their actions are represented in media which in turn, shapes public perception and affects the outcome of their demands. The study examines how American news platforms portray the 'Dark Indonesia' student protests, a recent social movement opposing Indonesian government policies, focusing on the representation of participants, actions, and events through the lens of transitivity in Systemic Functional Linguistics. As a major platform in global media, Voice of America English news has the power to impact not only domestic audiences, but also international communities. The purpose of the study is to uncover how language shapes the framing of the protests through an analysis of the verbs or processes used in each clause and how each social actor is represented through discursive strategies. The findings indicate that material verbs are the most dominant process used in the news. The ‘Dark Indonesia’ student protests representation is emphasized through their direct actions. The study argues that this linguistic focus on material processes justifies the protests by highlighting the significance of the movement and emphasizing the legitimacy of the protests in the eyes of the global audience.